The effect of rice husk ash fillers on processability of ABS impact modified PVC-U - Hassan, Azman; Sivaneswaran, K. (2002)
A bstract Rice husk ash (RHA) fillers were added to ABS impact modified PVC-LJ in order to reduce cost and maintain or improve properties. Rice husk can also act as reinforcing fillers at certain optimum level o f loading. As fusion behavior o f filled impact modified PVC-U play a dominant role in the processing operations and in the development o f the characteristics processed material due to fusion has a profound influence on mechanical, physical and chemical properties. Based on the literature review, no work has been reported the effect o f RHA fillers and the effect o f various coupling agents on fusion behavior o f PVC-U compound Thus, a processability study was conducted to investigate the fusion behavior o f filled impact modified PVC-U by using Brabender Plasticorder with fitted mixing head. In such cases, here is an attempt to analyze and compare the effect o f the RHA loading and various types o f coupling agents on the fusion behavior o f impact modified PVC-U. Work was carried out on the pre-prepared RHA, with different loading level. Analysis o f the results showed that 10 phr RHA filled impact modified PVC-U samples has shorter fusion time and higher fusion torque compared the other level o f filler loading. Zirconate treated samples showed longer fusion time and lower processing torque compared to the other types o f coupling agents. The experimental results also relate that the low loading o f the filler the faster fusion during processing.